TEACHER’S QUESTIONING STRATEGIES DURING THE ENGLISH CLASSROOM INTERACTION - Nabila Sri Agustina; Ridha Ilma; Deta Desvitasari (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
Interaction is a crucial component of interactive learning, and teachers often use questions to foster meaningful engagement. This study investigates the questioning strategies employed by an 8th-grade English teacher at one of Palembang's Islamic Junior High Schools. The study used one teacher at that school as a participant due to the focus on gaining a deep, detailed understanding of the questioning strategies employed in a specific classroom context. Using a qualitative case study design, data were collected through non-participant classroom observations and semi-structured interviews. Observations documented the teacher's questioning techniques in various instructional scenarios, while interviews explored their intentions and perspectives. Thematic analysis was used to analyse the data to achieve patterns and to categorize the types of questions. The finding revealed the teacher's three main questioning strategies: procedural, convergent, and divergent. Convergent questions, which required brief or yes/no responses, were the most frequently used, while procedural and divergent questions appeared less often. The teacher employed these strategies to maintain student interest, encourage critical thinking, focus on lesson content, assess understanding, clarify responses, and promote participation. These results emphasize the importance of questioning in fostering classroom interaction and provide valuable insights for enhancing teaching practices.